Meta Analisis Pengaruh Latihan Drill terhadap Kemampuan Passing Bawah Bola Voli - Anggina, Rahma Dea Dwi; Nugraha, Ugi; Muzaffar, Ahmad (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to re-analyze the use of drill training methods on volleyball underhand passing ability. The population in this study is a scientific publication article in the form of a national-scale journal in Indonesia about the effect of drill training on volleyball underhand passing ability from 2016-2024. The sample used in this study is about the effect of drill training on volleyball underhand passing ability. With a purposive sampling technique. The method used in this study is meta-analysis. The data analysis carried out is a quantitative descriptive analysis expressed in numbers. The data obtained will be presented in the form of a table to make it easier to analyze and understand the data so that the data presented is more systematic. Researchers use the SPSS application to help analyze or process data analysis of research results. Based on the results of the drill training method, it can improve volleyball underhand passing ability from the lowest -0.07 to the highest 0.31.